Key aspects of safeguarding of shareholders with regard to authorized capital - Drnovšek, Gregor (Pravnik, 2015)
Authorized capital is considered a most flexible form of subscribed capital in-crease. Similar to an ordinary subscribed capital increase, the system of safeguarding of shareholders with regard to authorized capital is mostly aimed at preserving the shareholders' basic subscribed capital share, and safeguarding the shareholders from (commercial) dilution of their rights. Shareholders are safeguarded also in case of capital increase with contributions in-kind, with special provisions governing quantitative restrictions of authorized capital, and with a special regime governing the voidability of general-meeting resolutions.
Keywords: Das Kapital; delnice; delničarji; gospodarske družbe; kapital; podjetja